PENGARUH PENYIRAMAN AIR LIMBAH TEMPE SEBAGAI PUPUK ORGANIK TERHADAP PERTUMBUHAN TOMAT (Solanum lycopersicum) - St. Humaerah Syarif (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2022)
This study aims to determine the effect of organic fertilizer (tempeh wastewater) on the growth of tomato plants (Solanum lycopersicum). This study was experimental, compiled with a completely randomized design (RAL) pattern consisting of three treatments and three tests. Data analysis with variance analysis (ANOVA) and continued with the smallest real difference test (BNT). The results showed that watering tempeh wastewater at a dose of 400 ml showed growth in tomato plant height by 17.35% and the number of leaf blades by 10.33%. While at a dose of 600 ml it is 23.18% and the number of leaf blades is 13%. Based on the results of the study, it can be concluded that watering tempeh wastewater as an organic fertilizer has a very noticeable effect on the growth of tomatoes.